PENGARUH PENERAPAN E-FILING, E-BILLING DAN PENGETAHUAN PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI (STUDI KASUS KANTOR PELAYANAN PAJAK PRATAMA KARAWANG) - agisni, kiki -; Mahpudin, Endang (Peneliti.net, 2024)
The purpose of this study was to determine the effect of implementing e-Filing, eBilling and Tax Knowledge on Individual Taxpayer Compliance. This study uses a quantitative method with a correlational research design. The population in this study are individual taxpayers who have earned income, taxpayers who use eFiling and e-Billing to report their taxes and pay taxes. The results of this study are: (1) There is a positive and significant effect of eFiling on Individual Taxpayer Compliance (2) There is a negative and insignificant effect of e-Billing on Individual Taxpayer Compliance (3) There is a positive and significant effect of Tax Knowledge on Individual Taxpayer Compliance (4) There is a positive and significant effect of the Implementation of e-Filing, e-Billing and Tax Knowledge on Individual Taxpayer Compliance. Determinant coefficient (????2) Application of e-Filing, e-Billing and Tax Knowledge on Individual Taxpayer Compliance.